2020
DOI: 10.1002/ccd.28715
|View full text |Cite
|
Sign up to set email alerts
|

Management of stent underexpansion using intravascular lithotripsy—Defining the utility of a novel device

Abstract: Objectives: This study aimed to present a case series of patient treated for stent underexpansion resistant to conventional treatment with intravascular lithotripsy (IVL). Background: Stent underexpansion is a powerful predictor of long-term stent patency and correlates with unfavorable clinical outcomes. This case series demonstrates the utility of IVL in managing stent underexpansion resistant to conventional treatment. Methods: We describe a case series of patients with stent underexpansion due to calcific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Even though a few reports have been recently documented about the use of IVL to treat coronary stent underexpansion,[ 2 ] we assume this case is unique because, to our knowledge, there are only a few reports about the use of IVL for the treatment of freshly deployed underexpanded coronary stents. [ 3 4 5 ] Further, it illustrates an alternative safe and effective approach to deal with tight calcified lesions when there is a high risk of perforation. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Even though a few reports have been recently documented about the use of IVL to treat coronary stent underexpansion,[ 2 ] we assume this case is unique because, to our knowledge, there are only a few reports about the use of IVL for the treatment of freshly deployed underexpanded coronary stents. [ 3 4 5 ] Further, it illustrates an alternative safe and effective approach to deal with tight calcified lesions when there is a high risk of perforation. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a registry including 71 patients and a prospective study with 120 patients with calcified coronary lesions demonstrated the safety and effectiveness of the IVL technique ( 5 , 6 ). In some case series, IVL has been used with success in the case of stent underexpansion resistant to conventional approaches ( 7 , 8 ). Moreover, IVL was shown as a valuable option for modifying femoroiliac stenosis to facilitate delivery of a transfemoral Impella CP ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…All device approval studies performed to date have only included de novo coronary lesions. In this issue of the Journal, Yeoh et al 4 provide the largest case series published to date on IVL use for stent under‐expansion. Remarkably, in all 13 patients (half of whom had undergone balloon inflation with the very‐high pressure OPN balloon [SIS Medical, Switzerland]) IVL resulted in stent expansion increasing the minimum lumen area from 2.71 to 6.44 mm 2 , without any complications!…”
Section: Figurementioning
confidence: 99%
“…IVL will likely become the next treatment step before laser with contrast, assuming that the IVL balloon can be safely delivered to the target lesion. The study by Yeoh et al 4 suggests that IVL may become a panacea for stent under‐expansion, yet we should use IVL in a thoughtful and vigilant manner to ensure that it does not become Pandora's box!…”
Section: Figurementioning
confidence: 99%